(untitled) (Journal of the College of Basic Education, 2022)
Historical studies in the Islamic eras were concerned with giving the economic aspect clear attention as it is the lifeblood of the Arab Islamic state, especially during the Abbasid era. There is no doubt that the book The Image of the Earth by Ibn Hawqal (d. 367 AH) and despite being a geographical book, it contains within it economic aspects and Especially in Iraq, and among the most important of these economic activities is agriculture, such as palm cultivation in Basra and on the banks of the Tigris and Euphrates rivers and near oases in the desert areas. Likewise, fruit trees are widely cultivated around rivers and in the city of Mosul and others in Iraq.